The Culture Industry and Participatory Audiences - Keltie, Emma. author. aut Link
IX, 152 p.
Keywords: This work offers a discussion of participatory culture as a disruption to the previously held dominance of the culture industry, while also exploring the tensions created in this emerging media landscape through analysis and examination of the current Australian media policy, regulation, and content distribution landscape. The text argues that the culture industry colonises participatory cultural practices and absorbs them into the practices of the industry, to reveal that what emerges from this colonisation is an audience that misrecognises their agency as participants in the production of culture. The discourse surrounding participatory culture positions the audience as active in cultural production and falsely emancipates them as consumers, with little acknowledgement of the exploitation of labour that is occurring. Keltie exposes how, as the culture industry folds participatory practices back into its own industry practices, audience participation, in effect, becomes authorised bythe culture industry. .